Bistable Epigenetic States Explain Age‐Dependent Decline in Mesenchymal Stem Cell Heterogeneity - Hamidouche, Zahia; Rother, Karen; Przybilla, Jens; Krinner, Axel; Clay, Denis; Hopp, Lydia; Fabian, Claire; Stolzing, Alexandra; Binder, Hans; Charbord, Pierre; Galle, Joerg (Stem cells (Dayton, Ohio), 2017)
The molecular mechanisms by which heterogeneity, a major characteristic of stem cells, is achieved are yet unclear. We here study the expression of the membrane stem cell antigen‐1 (Sca‐1) in mouse bone marrow mesenchymal stem cell (MSC) clones. We show that subpopulations with varying Sca‐1 expression profiles regenerate the Sca‐1 profile of the mother population within a few days. However, after extensive replication in vitro, the expression profiles shift to lower values and the regeneration time increases. Study of the promoter of Ly6a unravels that the expression level of Sca‐1 is related to the promoter occupancy by the activating histone mark H3K4me3. We demonstrate that these findings can be consistently explained by a computational model that considers positive feedback between promoter H3K4me3 modification and gene transcription. This feedback implicates bistable epigenetic states which the cells occupy with an age‐dependent frequency due to persistent histone (de‐)modification. Our results provide evidence that MSC heterogeneity, and presumably that of other stem cells, is associated with bistable epigenetic states and suggest that MSCs are subject to permanent state fluctuations. Stem Cells 2017;35:694–704 In young cells, expression of Sca‐1 is bistable. Frequent switches between high (Sca‐1H, red) and low (Sca‐1L, blue) expression states occur due to stochastic H3K4me3 (de‐) modification reactions at the gene promoter leading to gene expression heterogeneity. Accordingly, Sca‐1H and Sca‐1L populations regenerate the expression profile of their mother population (WCP) within a few days.During aging, gene activation by the underlying transcription factor network is reduced, stabilizing Sca‐1L states. Eventually, the system becomes monostable.